1995
DOI: 10.1017/s0956536100002169
|View full text |Cite
|
Sign up to set email alerts
|

Radiocarbon Chronology for the Late Archaic and Formative Periods on the Pacific Coast of Southeastern Mesoamerica

Abstract: Archaeological excavations carried out during the past five years along the Pacific coast of Mexico, Guatemala, and El Salvador have recovered 79 new 14C dates for the Late Archaic and Early to Middle Formative periods. We analyze these new dates along with 25 previously published dates to refine a sequence of 10 archaeological phases spanning almost three and a half millennia, from ca. 4000 to 650 B.C. The phases are summarized with a brief description of their most salient characteristics. We include illustr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
56
0
7

Year Published

1996
1996
2011
2011

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 77 publications
(65 citation statements)
references
References 4 publications
2
56
0
7
Order By: Relevance
“…We have used this approach to establish a new chronology for the site of Tlacuachero, a large shellmound site located on the Pacific coast of southwestern Mexico. Prior work at this site suggested that the bedded shell deposits accumulated between ~5500 and 4000 cal BP (Blake et al 1995;Voorhies 2004), but 14 C age reversals and large error margins prohibited a finer-grained chronology. We had assumed that this large shellmound accumulated gradually over a ~1500-yr period.…”
Section: Discussionmentioning
confidence: 93%
“…We have used this approach to establish a new chronology for the site of Tlacuachero, a large shellmound site located on the Pacific coast of southwestern Mexico. Prior work at this site suggested that the bedded shell deposits accumulated between ~5500 and 4000 cal BP (Blake et al 1995;Voorhies 2004), but 14 C age reversals and large error margins prohibited a finer-grained chronology. We had assumed that this large shellmound accumulated gradually over a ~1500-yr period.…”
Section: Discussionmentioning
confidence: 93%
“…Cerro de las Conchas, the oldest of the six late Archaic period middens in the Soconusco region, was deposited between 4000 and 3000  (Blake et al, 1995;Clark, 1994). This shell midden is approximately 80 m in diameter and over 5 m high.…”
Section: The Chantuto Peoplementioning
confidence: 99%
“…An underlying assumption is the near synchronous appearance of defining traits in different places. This is apparent in the way radiocarbon has been used to date some of this material (Blake et al, 1995). To deal with the association problem (severe in this case because of stratigraphic complexities), a statistical program has been adopted to eliminate all significant outliers from the mean of all 14C determinations associated with a particular kind of ceramic.…”
Section: The Case For Luminescence Datingmentioning
confidence: 99%